2013
DOI: 10.1111/pai.12078
|View full text |Cite
|
Sign up to set email alerts
|

Early fish introduction and neonatal antibiotics affect the risk of asthma into school age

Abstract: BackgroundThe early introduction of fish has been reported to reduce the risk of wheezing disorder in early childhood, while broad-spectrum antibiotics in the first week have been associated with an increased risk. However, it is uncertain whether the effects remain into school age. The aim was to explore these risk factors for doctor-diagnosed asthma at 8 years.MethodsData were obtained from a prospective, longitudinal study of a cohort of children born in western Sweden. The parents answered questionnaires a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 30 publications
11
71
1
2
Order By: Relevance
“…Conversely, DOGARU et al [137] found no clear evidence of a protective effect of breastfeeding against allergic rhinoconjunctivitis in children in the Leicester (UK) cohort study. GOKSÖ R et al [138] confirmed that the protective effect of early (before 9 months of life) fish introduction into an infant's diet against wheezing in early childhood is also present for atopic asthma at school age. A recent systematic review, however, concluded that the evidence is inconsistent from the epidemiological studies investigating the effects of fish intake during infancy and childhood on atopic outcomes in infants or children, and that further studies are needed [139].…”
Section: Paediatric Respiratory Epidemiologysupporting
confidence: 53%
See 1 more Smart Citation
“…Conversely, DOGARU et al [137] found no clear evidence of a protective effect of breastfeeding against allergic rhinoconjunctivitis in children in the Leicester (UK) cohort study. GOKSÖ R et al [138] confirmed that the protective effect of early (before 9 months of life) fish introduction into an infant's diet against wheezing in early childhood is also present for atopic asthma at school age. A recent systematic review, however, concluded that the evidence is inconsistent from the epidemiological studies investigating the effects of fish intake during infancy and childhood on atopic outcomes in infants or children, and that further studies are needed [139].…”
Section: Paediatric Respiratory Epidemiologysupporting
confidence: 53%
“…Finally, in the context of the PASTURE (Protection against Allergies Study in Rural Environments) birth cohort study conducted in five European countries, RODUIT et al [140] showed that an increased diversity of foods introduced in the first year of life had a significant protective effect against the later development of asthma, food allergy and food sensitisation, and that reduced food diversity was associated with reduced expression of Foxp3. Although the studies by GOKSÖ R et al [138] and RODUIT et al [140] were conducted in prospective birth cohorts and adjusted for confounders, reverse causation cannot be completely excluded.…”
Section: Paediatric Respiratory Epidemiologymentioning
confidence: 99%
“…This meant that 65% of the children with asthma at eight years of age were classified as having atopic asthma and 35% as having nonatopic asthma (14). In a study, on children aged seven to eight years of age from northern Sweden (30), 64.9% of the participants with asthma had allergic sensitisation based on a skin prick test.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic sensitisation in terms of a positive allergy test was reported in 84% of the subjects with atopic asthma. Specific information regarding these questions has been published previously (14). …”
Section: Methodsmentioning
confidence: 99%
“…For example, compared to conventional treatment, anthroposophic treatment of primary care patients with acute respiratory and ear symptoms had more favourable outcomes, lower antibiotic prescription rates, less adverse drug reactions, and higher patient satisfaction [28]. Moreover, the introduction of CAM medicinal products might overcome the related side effects of antibiotic use in childhood as several studies show that both maternal and child's use of antibiotics were associated with an increased risk of eczema or asthma [2931]. …”
Section: Cam Alternatives To Antibioticsmentioning
confidence: 99%